Differences in Management of Coronary Artery Disease in Patients With Medicare Advantage vs Traditional Fee-for-Service Medicare Among Cardiology Practices - Figueroa, Jose F. (JAMA Cardiol, 2019)
IMPORTANCE: One-third of Medicare beneficiaries are enrolled in Medicare Advantage (MA), Medicare’s private plan option. Medicare Advantage incentivizes performance on evidence-based care, but limited information exists using reliable clinical data to determine whether this translates into better quality for patients with coronary artery disease (CAD) enrolled in MA compared with those enrolled in traditional fee-for-service (FFS) Medicare. OBJECTIVE: To determine differences in evidence-based secondary prevention treatments and intermediate outcomes among patients with CAD enrolled in MA vs FFS Medicare. DESIGN, SETTING, AND PARTICIPANTS: In this observational, retrospective, cohort study, deidentified data from patients 18 years or older diagnosed as having CAD between January 1, 2013, and May 1, 2014, at cardiology practices participating in the Practice Innovation and Clinical Excellence (PINNACLE) registry were studied, including 35 563 patients enrolled in MA and 172 732 enrolled in FFS Medicare. Data were analyzed from March to July 2018. EXPOSURES: Medicare Advantage enrollment. MAIN OUTCOMES AND MEASURES: Medication prescription patterns among eligible patients and intermediate outcomes, including blood pressure and low-density lipoprotein cholesterol. RESULTS: Of the 35 563 patients with CAD enrolled in MA, 20 193 (56.8%) were male, and the mean (SD) age was 76.7 (7.6) years; of the 172 732 patients with CAD enrolled in FFS Medicare, 100 025 (57.9%) were male, and the mean (SD) age was 77.5 (8.0) years. Patients enrolled in MA were younger, less likely to be white, and more likely to be female and to have heart failure, diabetes, and chronic kidney disease compared with those enrolled in FFS Medicare. Compared with FFS Medicare beneficiaries, MA beneficiaries were more likely to receive secondary prevention treatments, including β-blockers (80.6% vs 78.8%; P < .001), angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers (70.7% vs 65.1%; P < .001), and statins (68.4% vs 64.5%; P < .001). Patients enrolled in MA were also more likely to receive all 3 medications when eligible (48.9% vs 40.4%; P < .001). After adjustment, MA beneficiaries had higher odds of receiving guideline-recommended therapy compared with FFS Medicare beneficiaries for β-blockers (odds ratio, 1.10; 95% CI, 1.04-1.17; P = .002), angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers (odds ratio, 1.13; 95% CI, 1.08-1.19; P < .001), and all 3 medications (odds ratio, 1.23; 95% CI, 1.001-1.50; P = .047). There were no significant differences in intermediate outcomes between those enrolled in MA and FFS Medicare, including systolic and diastolic blood pressure and low-density lipoprotein cholesterol levels. CONCLUSIONS AND RELEVANCE: Among patients with CAD in the PINNACLE registry, MA beneficiaries had more comorbidities than FFS Medicare beneficiaries and were more likely to receive secondary prevention treatments. However, this did not translate into differences in intermediate outcomes. These findings suggest that MA plans may drive improvements in process-based quality measures for Medicare beneficiaries, although this may have a limited effect on improving patient outcomes over FFS Medicare.